ADVANTAGES AND DISADVANTAGES OF USING GOOGLE CLASSROOM DURING COVID-19 PANDEMIC AT ONE PESANTREN AT MUARO JAMBI - Lamhot Sihombing (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2022)
ABSTRACK This research aims to explore Advantages And Disadvantages of student perspective using Google Classroom on online Learning the research is set at pondok Pesantren Hiddayatullah Sengeti Muaro Jambi with nine grade students as the subject. The methodology of this research is descriptive qualitative. The sample of this research is the nine grade of IX. The sample in this study used purposive sampling. During the Covid-19 pandemic, online learning has been widely used in process learning. One of the applications used for online learning is Google Classroom. However, Google Classroom has Advantage and Disadvantages that have not been studied especially from the student's point of view. Data were collected using interviews supported by an interview protocol. Data were analyzed using thematic analysis. From the data analysis, several themes emerged: 1.Google Classroom as the main platform for learning powered by WhatsApp 2. Google drive full of difficult to send assignments 3. Paperless submission. 4. Ease to see assessment. 5. Real time notifications. 6. Lack of interaction: a. There is no discussion and , b. No peer review ,and 7. Lack of motivation. Keyword : Google Classroom, Advantage and disadvantage of Google Classroom,Student Perspective, Online Learning , Covid-19